Chromosome instability in diffuse large B cell lymphomas is suppressed by activation of the noncanonical NF‐κB pathway. Issue 10 (11th November 2014) - Ramachandiran, Sampath; Adon, Arsene; Guo, Xiangxue; Wang, Yi; Wang, Huichen; Chen, Zhengjia; Kowalski, Jeanne; Sunay, Ustun R.; Young, Andrew N.; Brown, Theresa; Mar, Jessica C.; Du, Yuhong; et al.
<x xml:space="preserve">Abstract</x> Diffuse large B cell lymphoma (DLBCL) is the most common form of lymphoma in the United States. DLBCL comprises biologically distinct subtypes including germinal center‐like (GCB) and activated‐B‐cell‐like DLBCL (ABC). The most aggressive type, ABC‐DLBCL, displays dysregulation of both canonical and noncanonical NF‐κB pathway as well as genomic instability. Although, much is known about the tumorigenic roles of the canonical NF‐kB pathway, the precise role of the noncanonical NF‐kB pathway remains unknown. Here we show that activation of the noncanonical NF‐κB pathway regulates chromosome stability, DNA damage response and centrosome duplication in DLBCL. Analysis of 92 DLBCL samples revealed that activation of the noncanonical NF‐κB pathway is associated with low levels of DNA damage and centrosome amplification. Inhibiting the noncanonical pathway in lymphoma cells uncovered baseline DNA damage and prevented doxorubicin‐induced DNA damage repair. In addition, it triggered centrosome amplification and chromosome instability, indicated by anaphase bridges, multipolar spindles and chromosome missegregation. We determined that the noncanonical NF‐κB pathway execute these functions through the regulation of GADD45α and REDD1 in a p53‐independent manner, while it collaborates with p53 to regulate cyclin G2 expression. Furthermore, this pathway regulates GADD45α, REDD1 and cyclin G2 through direct binding of NF‐κB sites to their promoter region. Overall, these results indicate that the noncanonical NF‐κB pathway plays a central role in maintaining genome integrity in DLBCL. Our data suggests that inhibition of the noncanonical NF‐kB pathway should be considered as an important component in DLBCL therapeutic approach.